A dynamic analysis of nonpoint pollution control instruments in agriculture. (25th January 2007) - Martinez, Yolanda; Calvo, Elena; Albiac, Jose
Nonpoint pollution from agriculture is an emerging issue in the environmental policy of the European Union. Dynamic optimisation techniques are important in nonpoint pollution, and neglect of dynamic aspects may seriously mislead the proper design of policy measures. This paper presents an empirical assessment of nitrogen pollution abatement in the Ebro basin of northeastern Spain. The aim is to contribute to the ongoing policy discussion by ranking several emission control measures. Results indicate that nitrogen-based instruments are more cost efficient than water-based instruments. This finding questions the reliance of the Water Framework Directive on water pricing to improve water quality. The study also provides welfare, quasi-rent and pollution information for each crop and control measure. This information could be useful when discriminating abatement measures by crop type, in cases of valuable ecosystems and heavy nitrogen damage costs.